Application of the Fourier Method to The Study of Boundary Problems for Second and Third Order Elliptic-Hyperbolic Type Equations - Ruziyeva Tokhtagul Jumaboy kizi (Euro Asian Journal Publishing, 2024)
Boundary problems for second and third-order elliptic-hyperbolic type equations are an important area of study in partial differential equations. These boundary value problems involve equations that exhibit both elliptic and hyperbolic behavior, leading to unique mathematical challenges.
Keywords: boundary problems; second-order; elliptic-hyperbolic type